2020
DOI: 10.1016/j.eats.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lemaire Lateral Extra-articular Tenodesis in the Pediatric Patient: An Adjunct to Anterior Cruciate Ligament Reconstruction

Abstract: Recent literature has identified a population of active adolescents aged 13 to 15 years who are at high risk for anterior cruciate ligament graft rupture. Addressing the anterolateral complex during primary anterior cruciate ligament reconstruction has recently re-emerged in the literature, with various techniques available. This paper aims to describe a lateral extra-articular tenodesis procedure using the iliotibial band with a modified Lemaire technique. This procedure is recommended for active adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…The indications, contraindications, techniques and outcomes of AEAPs are evolving but the current literature supports their use in the reduction of graft failure rates and improvements in rotational stability. 71 , 72 Rates of re-rupture are the highest in children and the routine addition of AEAPs has been suggested for the skeletally immature, although the absence of rotational stability is not necessarily the cause of higher failure rates.…”
Section: Aeapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indications, contraindications, techniques and outcomes of AEAPs are evolving but the current literature supports their use in the reduction of graft failure rates and improvements in rotational stability. 71 , 72 Rates of re-rupture are the highest in children and the routine addition of AEAPs has been suggested for the skeletally immature, although the absence of rotational stability is not necessarily the cause of higher failure rates.…”
Section: Aeapsmentioning
confidence: 99%
“…The current literature favors the addition of an AEAP in patients with two or more risk factors, namely, hyperlaxity, over 10 degrees of recurvatum, evidence of high-grade pivoting injury (meniscus tears, lateral compartment osteochondral trauma, multi-ligament injuries) and involvement in pivoting, collision, or contact sports. 71 , 72 , 76 Another indication for AEAPs in the pediatric setting may be very young children who have a limited rehabilitation capacity and poor neuromuscular control. 77 …”
Section: Aeapsmentioning
confidence: 99%
“…Recently, LET has been used in addition to ACLR to add restriction to internal tibial rotation forces, 4 and different authors have shown their techniques to achieve this task. 5 , 6 , 7 , 8 , 9 Also, biomechanical studies have compared different techniques for LET procedures. 10 …”
mentioning
confidence: 99%
“…4 Recently, LET has been used in addition to ACLR to add restriction to internal tibial rotation forces, 4 and different authors have shown their techniques to achieve this task. [5][6][7][8][9] Also, biomechanical studies have compared different techniques for LET procedures. 10 This article aims to describe our technique performing a modified Macintosh LET as an addition to ACLR in selected patients who require extra internal tibial rotation control.…”
mentioning
confidence: 99%
“… 12 Many different techniques for LET have been described, with the (modified) Lemaire technique being widely favored. 13 , 14 , 15 The recent literature does report that LET leads to a reduction in persistent rotatory laxity and ACL graft rupture rate, 16 , 17 but also may be associated with increased pain, reduced quadriceps strength, reduced subjective functional recovery, and cosmetic complaints. 18 Thus this article aims to describe our minimally invasive technique for a modified Lemaire tenodesis.…”
mentioning
confidence: 99%